(untitled) (Research, Society and Development, 2022)
With the new model of remote teaching, it was necessary to insert tools that would help the teacher in their methodologies and therefore make the students act in a more direct and participatory way. Didactic games are tools that help in the teaching process, so the present study aims to analyze the use of QUIZ developed in Wordwall®, to fix Biology content with students from a High School in the city of Parnaíba-PI. The methodological matrix of this work was based on the application of a Quiz entitled "virus copy", where it was applied after the content taught with the help of a link that directed the students to the Word wall platform, it showed the progress of hits and misses, and at the end a score ranking was generated. The application of the Quiz through the word wall platform proved to be very effective, it was possible to instigate the participation of practically all students, even the less active students. Through the tool, the students reported that they compared this way of fixing the subject as a joke, which made the learning moment more fun and interesting. The application of online digital games has been favoring the teaching-learning process both for the student who fixes the content better and for the teacher who can observe how their students are learning.